Application of Google Classroom in Islamic Religious Education at the Integrated Model Public High School in Palu City - Andi Ardiansyah; Hendriana Sri Rejeki; Naima Naima; Emy Erwhana; Erni Irmayanti (AL-ISHLAH: Jurnal Pendidikan, 2023)
Learning processes are facilitated by means of technological technique. Educators in the age of Industry 4.0 need the tools to keep up with the rapid pace of technological change. The low enrollment in Islamic religious education courses at the secondary level is one issue that Google Classroom is aiming to address. The researchers at Palu City's Integrated Model Public High School wanted to know how they might best use Google Classroom to teach Islamic religious education. There were a total of 47 participants, including 27 male and 20 female students, and data was gathered from them using interview, observation, and documentation procedures. The findings of this study have the potential to expand our understanding of Islamic religion and, more specifically, the ways in which Google Classroom can be used to teach subjects within the realm of Islamic religious education. They can also serve as a point of reference in the literature of the education and university sectors, providing guidance as policymakers consider how best to implement such ideas. The findings revealed that Google Classrooms in the field of Islamic Religious Education help researchers gain experience and the skills they need to apply that experience in society, and also provide a knowledge contribution to the field in the form of a discourse model for teaching and learning in the field of Islamic Religious Education.